Electrospinning parameters for organic polymers for nanofiber production - Khor, Ken Hwan (2014)
Nanofibre is a type of fibre with the sizes of nano scale. It can be produced by several methods but the most conventional way is by electrospinning process. Electrospinning process is using the concept of different charges between the collector and the solution and therefore from the tips of the Taylor cone shoot out jet of fibre to the collector and thus, nanofibre is produced. There are several parameters which will affect the morphology of the nanofibre. Among is the applied voltage, capillary to ground distance, concentration of the solution, volatility of the solution and also the conductivity of the solution. Nanofibre has been used in biomedical field, filtration, protective material, sensors, nanofibre reinforced composites and many more. In this research, polyethylene oxide (PEO) will be used as the material to fabricate the nanofibre and aim to fabricate out linear shape nanofibre. The PEO solution is prepared by dissolving the PEO powder into solvent whether is water or ethanol and stirred for more than 8 hours using magnetic stirrer for the solution to reach homogeneous state. Then the solution will undergo electrospinning process. The nanofibre which have been fabricate will undergo field emission scanning electron microscopy (FESEM) to study the morphology of the nanofibre. From the result that have obtained, it is clearly that with 5wt% of 900k MW of PEO mix with 5wt% of ethanol as solvent will fabricate out linear shape nanofibre